Catalysing Actionable Knowledge for Digitalisation in ACP Agribusiness: CTA's Director - Hailu, Michael (Technical Centre for Agricultural and Rural Cooperation, 2018)
Michael Hailu shares the objectives and expected outcomes of the workshop